Effectiveness of Audit Committees in Southeast Asia: Perspectives of External Auditors - Sewell, David Leonard (2009)
Up till 10 years ago, the words Corporate Governance was hardly heard despite corporate scandals such as Bearings and BCCI that occurred in the early 1990s. One major reason was that 20 years prior to the Asian financial crisis in 1997, most Asian countries enjoyed unprecedented growth in their economies. Seemed like corporate governance was something people were generally not concerned with when times were good. In 1997, financial crisis had hit Asia like a tsunami; stock markets in the region had tumbled and their currencies had devalued against major international currencies such as the US dollar. Theories on why the crisis occurred ranged from inept macroeconomic policy (Greenspan, 1998) to malpractices by the banking sector (Krugman, 1998). At the microeconomic level, many companies were in dire straits from the start of the crisis in 1997 till 2000, with quite a number ending up in bankruptcy (such as the famous TPI group in Thailand and chaebols in Korea). Cronyism, nepotism, lack of accountability and inadequate risk management were some of the reasons cited for corporate failures.